Impact of chilling accumulation and hydrogen cyanamide on floral organ development of sweet cherry in a warm region - Lei WANG; Lu ZHANG; Chao MA; Wen-ping XU; Zong-rang LIU; Cai-xi ZHANG; Whiting D. Matthew; Shi-ping WANG (Journal of Integrative Agriculture, 2016)
The microscopic investigation of the floral development of sweet cherry (Prunus avium L. cv. Hongdeng) from a warm winter climate (Shanghai) and cold winter climate (Tai’an, Shandong Province, China) was conducted to explore the reason of low fruit set. The effect of hydrogen cyanamide (HCN) on floral development under warm winter conditions was also investigated. Trees grown in Shanghai with insufficient chilling accumulation exhibited little difference in the progression of microspore development compared to trees in Tai’an that accumulated adequate chilling, but showed substantial delays in ovule and embryo sac development. The growth of nucelli did not proceed beyond the macrospore mother cell and macrospore stages with abortion rates of 13, 15 and 45% by 6, 3 and 0 d before full bloom, respectively. These abnormalities in the ovule and embryo sac in the Shanghai-grown trees were eliminated by HCN application. These results suggest that chilling regulates the development of female floral organs in winter dormancy; therefore, insufficient chilling accumulation, causing abnormality of the female floral organs, restricts the cultivation of sweet cherry in warm winter regions. Interestingly, HCN application, which decreased the chilling requirements for Hongdeng, may be a potential strategy for sweet cherry cultivation in warm winter regions.